Preparation method of phosphorus-nitrogen composite carrier-free flame-retardant master batch
By coating and modifying the powder flame retardant, the degradation foaming and scale problems of organic phosphinate and melamine polyphosphate in the application of engineering plastic reinforced glass fiber are solved, which significantly improves the dispersion and compatibility of the material and maintains the mechanical properties of the material.
Patent Information
- Application Number
- CN202411946828.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-14
AI Technical Summary
In the application of engineering plastic reinforced glass fiber, organic phosphinate and melamine polyphosphate have problems in degradation of foaming and injection molding during processing, and alkaline acid absorbents have a great impact on the mechanical properties of the materials.
Before preparing the carrier-free masterbatch, the powder flame retardant is coated and modified to improve its compatibility with the substrate, and to harmonize the organic phosphinate and polyphosphate to reduce their interactions and wear on the equipment.
Through double-layer coating treatment, the deterioration of hydroxide or oxide-based acid absorbents on the material is significantly alleviated, the dispersion of the flame retardant and the compatibility of the substrate are improved, the mold scale problem during the processing is reduced, and the mechanical properties of the material are maintained.
Smart Images

Figure BDA0005213863480000071 
Figure BDA0005213863480000081 
Figure BDA0005213863480000082
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic hypophosphite flame retardants, and in particular relates to a method for preparing a phosphorus-nitrogen composite carrier-free flame retardant masterbatch with good dispersibility. Background Art
[0002] As a commonly used flame retardant system, organic phosphinate compounded with melamine polyphosphate has the advantages of high flame retardancy and good comprehensive performance. However, in the application system of engineering plastics reinforced glass fiber, the compound use of the two will cause degradation and foaming during processing, as well as mold scale problems during injection molding. These phenomena are particularly obvious in the application of nylon materials. Based on this, many researchers will use some alkaline acid absorbers for neutralization and adjustment, which can alleviate the above problems to a certain extent. However, alkaline acid absorbers are mostly hydroxide or oxide flame retardants. These materials have a great influence on the mechanical properties of the material, and a small amount of them will have a great impact on the material.
[0003] In recent years, the development of carrier-free masterbatch has become increasingly popular. Its use is universal and does not require twin-screw granulation, which will not affect the mechanical properties of the material. However, the preparation of carrier-free masterbatch requires adjusting the hardness of the molded particles to ensure that they will not break during transportation and transport, but at the same time, they should not be too hard, which will result in uneven dispersion during the processing process. Summary of the invention
[0004] In order to solve the above technical problems, the present invention first coats and modifies the powder flame retardant before preparing the carrier-free masterbatch, which can improve its compatibility with the substrate, especially for hydroxide or oxide acid absorbers, the coating and modification treatment can significantly alleviate its deterioration effect on the material. On the other hand, the physical properties of the weak acid of the main component of the composite flame retardant (both organic phosphinate and polyphosphate are weakly acidic) are adjusted to a certain extent, and the organic phosphinate and polyphosphate are respectively coated with a double-layer coating material, which can weaken their mutual interaction, alleviate the wear and tear of the equipment caused by their weak acid characteristics, and better maintain the physical properties of the substrate.
[0005] The present invention provides a method for preparing a phosphorus-nitrogen composite carrier-free flame retardant masterbatch, which is characterized by comprising the following steps:
[0006] The phosphorus-nitrogen composite flame retardant is stirred at high speed by a high-speed mixer and heated to 70-110 degrees, and an ester auxiliary agent and an alkaline coupling agent are added in sequence by spraying to carry out a coating reaction;
[0007] After the coating reaction is completed and the solvent is evaporated, the flame retardant powder is cooled to below 50 degrees, a lubricating dispersant and an adhesive are added, and the powder is stirred again at high speed by a high-speed mixer and heated to 80-120 degrees, and pressed into a carrier-free flame retardant masterbatch.
[0008] Preferably, the mass percentage of the phosphorus-nitrogen composite flame retardant is 90-95%, the mass percentage of the ester auxiliary agent is 0.5-1.5%, the mass percentage of the basic coupling agent is 0.5%-2%, the mass percentage of the lubricating dispersant is 0.5-1.5%, and the mass percentage of the adhesive is 2-5%.
[0009] Preferably, the phosphorus-nitrogen composite flame retardant is compounded from an organic phosphine flame retardant, a polyphosphate, and a combination or individual components formed by hydroxides and / or oxides; more preferably, the organic phosphorus is selected from one or more mixtures of diethyl aluminum phosphite, diethyl zinc phosphite, and diethyl-monoethyl composite aluminum phosphite; the polyphosphate is selected from one or more mixtures of ammonium polyphosphate, piperazine pyrophosphate, and melamine polyphosphate; the hydroxide is selected from one or more mixtures of magnesium hydroxide and aluminum hydroxide; the oxide is selected from one or more mixtures of zinc oxide and aluminum oxide.
[0010] More preferably, the organophosphorus flame retardant is aluminum diethylphosphinate, the polyphosphate is melamine polyphosphate, the combination or individual component formed by the hydroxide and / or oxide is a 1:1 composition of magnesium hydroxide and zinc oxide, and the proportion of the three is 50-80:20-50:0.5-3.
[0011] Preferably, the ester additive is selected from tetraethyl orthosilicate and butyl titanate additives.
[0012] Preferably, the alkaline coupling agent is selected from alkaline silane coupling agents, such as KH550, KH900, KH602 and the like.
[0013] Preferably, the lubricating dispersant is selected from one or more mixtures of zinc stearate, calcium stearate, glyceryl stearate, ethylene bisstearamide, silicone powder, oxidized polyethylene wax, montan wax and the like.
[0014] Preferably, the adhesive is selected from polyester-modified silicone additives, polyester-modified siloxane, pentaerythritol stearate, and oleic acid amide.
[0015] Preferably, the ester auxiliary agent is first dispersed in an alcohol solvent, a reaction molar equivalent of pure water is added, and the reaction is stirred at room temperature until the hydrolysis is completed.
[0016] Preferably, the alkaline coupling agent is first dispersed in an alcohol solvent, a reaction molar equivalent of pure water is added, and the reaction is stirred at room temperature until the hydrolysis is completed.
[0017] The present invention further provides a phosphorus-nitrogen composite carrier-free flame retardant masterbatch, which is prepared by the method as described above.
[0018] The present invention further provides the flame retardant application of the phosphorus-nitrogen composite carrier-free flame retardant masterbatch in a glass fiber reinforced system.
[0019] Preferably, the ratio of the glass fiber reinforcement system is:
[0020] PA6 resin 50-55%, antioxidant 0.4-0.5%, glass fiber 30%, carrier-free flame retardant masterbatch 15%-20%.
[0021] Beneficial effects of the present invention:
[0022] (1) The organic phosphite-compounded melamine polyphosphoric acid system has strong hydrophobicity and is not easy to be well and stably coated by conventional coupling agents. The ester additives first form polyacids after hydrolysis, and then can achieve a multiple cross-linked network structure under high temperature or alkali catalysis. It can be well coated on the surface of the organic phosphite-compounded melamine polyphosphoric acid system, and the formed cross-linked network can achieve better bonding with conventional coupling agents.
[0023] (2) Alkaline coupling agents have many functions. First, alkaline coupling agents can promote the condensation of polyacids formed by ester additives into a macromolecular network structure. Second, the organic phosphite-melamine polyphosphoric acid system has a weak acid property. After being blended with an alkaline coupling agent, the flame retardant system can be made acidic, thereby reducing the corrosion of equipment caused by the flame retardant during processing and application, as well as the mold scale problem caused by the injection molding process. Third, the introduction of organic groups in the alkaline coupling agent can improve the compatibility of the flame retardant component with the substrate, especially the poor compatibility of the acid absorber hydroxides and oxides with the substrate can be significantly improved.
[0024] (3) After double coating, the organic groups of the coupling agent can better combine with the lubricating dispersant and adhesive to achieve good bonding effect of the masterbatch. DETAILED DESCRIPTION
[0025] Example 1
[0026] The ester auxiliary agent used is tetraethyl orthosilicate, the proportion is 1%, the alkaline coupling agent is KH900, the proportion is 1%, the composite phosphorus nitrogen flame retardant proportion is 94%, wherein diethyl aluminum phosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide complex = 70:25:1.5, the dispersing lubricant is 1%, and the adhesive is 3%.
[0027] (1) Dispersing and hydrolyzing ethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of ethyl orthosilicate, water, and ethanol is 1:4:10, the reaction is carried out under magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0028] (2) The alkaline coupling agent KH900 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH900, water, and ethanol being 1:3:10. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0029] (3) Heat the composite phosphorus-nitrogen flame retardant (94%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 70 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary agent solution and alkaline coupling agent solution into the system in turn. Spray the alkaline coupling agent solution half an hour after the ester auxiliary agent solution is sprayed. After the spraying is completed, react again for half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0030] (4) Cool the powder from the previous step to below 50 degrees, add 1% dispersing lubricant and 3% binder, quickly stir and disperse evenly, then heat to 90 degrees, discharge and convey to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0031] Example 2
[0032] The ester auxiliary agent used is tetraethyl orthosilicate, the proportion is 1.2%, the alkaline coupling agent is KH602, the proportion is 1.3%, the composite phosphorus nitrogen flame retardant proportion is 93%, among which diethyl aluminum phosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide complex = 65:30:1.5, the dispersing lubricant is 1.5%, and the adhesive is 3%.
[0033] (1) Dispersing and hydrolyzing tetraethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of tetraethyl orthosilicate, water, and ethanol is 1:4:8, and reacting with magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0034] (2) The alkaline coupling agent KH602 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH602, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0035] (3) Heat and stir the composite phosphorus-nitrogen flame retardant (93%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary agent solution and alkaline coupling agent solution into the system in turn. Spray the alkaline coupling agent solution half an hour after the ester auxiliary agent solution is sprayed. After the spraying is completed, react again for half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0036] (4) Cool the powder from the previous step to below 50 degrees, add 1.5% of dispersing lubricant and 3% of binder, stir quickly to disperse evenly, then heat to 90 degrees, discharge the material and convey it to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0037] Example 3
[0038] The ester auxiliary agent used is butyl titanate, the proportion is 1%, the alkaline coupling agent is KH602, the proportion is 1%, the composite phosphorus nitrogen flame retardant proportion is 94%, wherein diethyl aluminum phosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide complex = 60:30:1.5, the dispersing lubricant is 1%, and the adhesive is 3%.
[0039] (1) Dispersing and hydrolyzing butyl titanate in anhydrous ethanol, the molar ratio of butyl titanate to ethanol is 1:10, reacting under magnetic stirring at room temperature for 1 hour until the dispersion is uniform, and preparing distilled water equivalent to 4 mol of butyl titanate for standby use;
[0040] (2) The alkaline coupling agent KH602 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH602, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0041] (3) Heat and stir calcium diethylphosphinate (94%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the dispersed ester additive, water and alkaline coupling agent solution into the system in sequence. After the dispersed ester additive is sprayed, immediately spray distilled water equivalent to 4 mol of butyl titanate. After stirring for half an hour, spray the alkaline coupling agent solution again. After spraying, react for another half an hour, adjust the temperature to 110 degrees, and evaporate the solvent.
[0042] (4) Cool the powder from the previous step to below 50 degrees, add 1% dispersing lubricant and 3% binder, quickly stir and disperse evenly, then heat to 100 degrees, discharge and convey to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0043] Example 4
[0044] The ester auxiliary agent used is tetraethyl orthosilicate, the proportion is 1.5%, the alkaline coupling agent is KH550, the proportion is 1%, the composite phosphorus nitrogen flame retardant proportion is 92%, wherein diethyl aluminum phosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide complex = 60:35:1.5, the dispersing lubricant is 1.5%, and the adhesive is 4%.
[0045] (1) Dispersing and hydrolyzing tetraethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of tetraethyl orthosilicate, water, and ethanol is 1:4:8, and reacting with magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0046] (2) The alkaline coupling agent KH550 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH550, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0047] (3) Heat and stir diethyl aluminum phosphinate (92%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary agent solution and alkaline coupling agent solution into the system in turn. Spray the alkaline coupling agent solution half an hour after the spraying of the ester auxiliary agent solution. After the spraying is completed, react again for half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0048] (4) Cool the powder from the previous step to below 50 degrees, add 1.2% dispersing lubricant and 3% binder, quickly stir and disperse evenly, then heat to 90 degrees, discharge and convey to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0049] Example 5
[0050] The ester auxiliary agent used is butyl titanate, the proportion is 1%, the alkaline coupling agent is KH602, the proportion is 1.2%, the composite phosphorus nitrogen flame retardant proportion is 94%, wherein diethyl aluminum phosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide complex = 66:33:1, the dispersing lubricant is 0.8%, and the adhesive is 3%.
[0051] (1) Dispersing and hydrolyzing butyl titanate in anhydrous ethanol, the molar ratio of butyl titanate to ethanol is 1:10, reacting under magnetic stirring at room temperature for 1 hour until the dispersion is uniform, and preparing distilled water equivalent to 4 mol of butyl titanate for standby use;
[0052] (2) The alkaline coupling agent KH602 was dispersed and hydrolyzed in a water-ethanol solution, with the molar ratio of KH602, water, and ethanol being 1:3:8. The reaction was carried out under magnetic stirring at room temperature for 2 h until the hydrolysis was basically completed.
[0053] (3) Heat and stir aluminum diethylphosphinate (94%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 80 degrees, increase the speed to 1000 r / min, and spray the dispersed ester additive, water and alkaline coupling agent solution into the system in sequence. After the dispersed ester additive is sprayed, immediately spray distilled water equivalent to 4 mol of butyl titanate. After half an hour of stirring, spray the alkaline coupling agent solution again. After spraying, react for another half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0054] Comparative Example 1
[0055] A composite phosphorus-nitrogen flame retardant, wherein aluminum diethylphosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide complex = 70:25:1.5, is put into a high-speed mixer for mixing at a mixing speed of 500 rpm for 10 minutes and is ready for use;
[0056] Comparative Example 2
[0057] No ester auxiliary agent and alkaline coupling agent are used, the ratio of composite phosphorus-nitrogen flame retardant is 95%, wherein aluminum diethylphosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide composite is 70:25:1.5, the dispersing lubricant is 1%, and the adhesive is 4%.
[0058] (1) At room temperature, add a composite phosphorus-nitrogen flame retardant (95%), a dispersing lubricant (1%) and a binder (4%) into a high-speed mixer, stir and disperse them uniformly quickly, then heat to 90 degrees, discharge the material and convey it to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0059] Comparative Example 3
[0060] Only ester auxiliary agent ethyl orthosilicate is used, the proportion is 1%, the proportion of composite phosphorus nitrogen flame retardant is 95%, among which diethyl phosphinate aluminum: melamine polyphosphate: magnesium hydroxide and zinc oxide complex = 70:25:1.5, the dispersing lubricant is 1%, and the adhesive is 3%.
[0061] (1) Dispersing and hydrolyzing ethyl orthosilicate in a water-ethanol solution, wherein the molar ratio of ethyl orthosilicate, water, and ethanol is 1:4:10, the reaction is carried out under magnetic stirring at room temperature for 2 hours until the hydrolysis is substantially completed.
[0062] (2) Heat and stir the composite phosphorus-nitrogen flame retardant (95%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 70 degrees, increase the speed to 1000 r / min, and spray the hydrolyzed ester auxiliary solution into the system. After the ester auxiliary solution is sprayed, react for another half an hour, and adjust the temperature to 110 degrees to evaporate the solvent.
[0063] (4) Cool the powder from the previous step to below 50 degrees, add 1% dispersing lubricant and 3% binder, quickly stir and disperse evenly, then heat to 90 degrees, discharge and convey to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0064] Comparative Example 4
[0065] Only alkaline coupling agent KH550 is used, the proportion is 1%, the proportion of composite phosphorus nitrogen flame retardant is 95%, wherein diethyl aluminum phosphinate: melamine polyphosphate: magnesium hydroxide and zinc oxide composite = 70:25:1.5, the dispersing lubricant is 1%, and the adhesive is 3%.
[0066] (1) The alkaline coupling agent KH550 was dispersed and hydrolyzed in a water-ethanol solution, the molar ratio of tetraethyl orthosilicate, water, and ethanol was 1:3:10, and the reaction was carried out under magnetic stirring at room temperature for 2 hours until the hydrolysis was basically completed.
[0067] (3) Heat and stir diethyl aluminum phosphinate (95%) in a high-speed mixer at a speed of 500 r / min. After the temperature reaches 70 degrees, increase the speed to 1000 r / min, spray the alkaline coupling agent solution that has been hydrolyzed into the system, react again for half an hour after spraying, and adjust the temperature to 110 degrees to evaporate the solvent.
[0068] (4) Cool the powder from the previous step to below 50 degrees, add 1% dispersing lubricant and 3% binder, quickly stir and disperse evenly, then heat to 90 degrees, discharge and convey to a roller press for extrusion granulation to obtain a carrier-free flame retardant granule product for standby use.
[0069] Example 6
[0070] Taking the flame retardant application of PA6 glass fiber reinforced system as an example, the products prepared in the above preparation example are added as follows:
[0071] PA6 resin 50-55%, antioxidant 0.4-0.5%, glass fiber 30%, carrier-free flame retardant particles 15%-20% in each case, raw materials except glass fiber are mixed in a high-speed mixer and added to the feed port, glass fiber is added through the glass fiber inlet, and the processing temperature of the twin-screw extruder is set to 210-235 degrees. The flame-retardant reinforced modified particles are prepared by strand pelletizing, and after the particles are dried, they are molded by an injection molding machine to prepare various required test strips.
[0072] The physical properties tested in the comprehensive performance table are as follows:
[0073] The test methods for tensile strength and elongation at break of materials are determined in accordance with GB / T1040-2018 Plastics—Determination of tensile properties;
[0074] The material bending strength test method is determined according to GB / T 9341-2008 (three-point bending) standard for the determination of plastic bending properties;
[0075] The material impact strength test method is determined according to GB / T 1843-2008 Plastic Izod Beam Impact Strength Test Standard;
[0076] The material melt index test method is determined according to GB / T3682-2000 Thermoplastic Plastic Melt Mass Flow Rate and Melt Volume Flow Rate Test Standard;
[0077] The vertical combustion test method of the material is determined according to the horizontal and vertical methods of GB / T 2408-2008 Plastics Combustion Performance Determination Standard.
[0078] Table 1 is the processing record of flame retardants of Examples 1-5 and Comparative Examples 1-4;
[0079] Table 2 shows the processing formulas of flame retardant applications of Examples 1-5 and Comparative Examples 1-4, and the serial numbers correspond to the numbers of the above-mentioned preparation examples in sequence;
[0080] Table 3 shows the test results of the flame retardant application of Examples 1-5 and Comparative Examples 1-4, and the serial numbers correspond to the above-mentioned preparation example numbers.
[0081] Table 1
[0082]
[0083] Note: (1) Particle stability is measured by mixing the material in a high-speed mixer to see how the uncarrier masterbatch breaks up.
[0084] (2) The color of the original color plate is light yellow to white and is a qualified color plate. The gray color plate is caused by the weak acidity of the product, which leads to the decomposition of the base material.
[0085] (3) For ultra-thin plates (0.4 mm), the dispersion can be observed under light to see if there are any white spots with poor dispersion;
[0086] (4) The color of the original color plate is light yellow to white and is a qualified color plate. The gray color plate is caused by the weak acidity of the product, which leads to the decomposition of the base material.
[0087] Table 2
[0088]
[0089] Table 3
[0090]
[0091]
[0092] From the processing record table in Table 1, we can see that compared with the masterbatch prepared by powder, no coating or single-layer coating, the masterbatch prepared by double-layer coating has better particle stability, smooth material feeding, and can improve production efficiency during the application of twin-screw processing. In addition, the dispersion of the flame retardant component of the formed thin material was compared and observed. The masterbatch prepared by double-layer coating has good compatibility with the substrate, stable processing, and the natural color plate shows a more stable color, which is convenient for color matching of various colors.
[0093] From the comprehensive performance test table in Table 3, it can be concluded that the flame-retardant glass fiber reinforced materials prepared by processing masterbatch or powder flame retardant have the following mechanical properties and flame retardancy: the masterbatch prepared after double-layer coating is the best, the alkaline coupling agent coating is better, the masterbatch prepared after single-layer coating of ester additives and the masterbatch prepared directly without coating have similar performance, and the performance of the powder added directly is poor. Because the double-layer coating provides better dispersibility and compatibility with the substrate, it achieves good mechanical properties and stable flame retardant properties.
Claims
1. A method for preparing a phosphorus-nitrogen composite carrier-free flame retardant masterbatch, characterized in that: The steps include: The phosphorus-nitrogen composite flame retardant is stirred at high speed by a high-speed mixer and heated to 70-110 degrees, and an ester auxiliary agent and an alkaline coupling agent are added in sequence by spraying to carry out a coating reaction; After the coating reaction is completed and the solvent is evaporated, the flame retardant powder is cooled to below 50 degrees, a lubricating dispersant and an adhesive are added, and the powder is stirred again at high speed by a high-speed mixer and heated to 80-120 degrees, and pressed into a mold to obtain a carrier-free flame retardant masterbatch; The mass percentage of the phosphorus-nitrogen composite flame retardant is 90-95%, the mass percentage of the ester auxiliary agent is 0.5-1.5%, the mass percentage of the basic coupling agent is 0.5%-2%, the mass percentage of the lubricating dispersant is 0.5-1.5%, and the mass percentage of the adhesive is 2-5%.
2. The preparation method according to claim 1, characterized in that The phosphorus-nitrogen composite flame retardant is compounded from an organic phosphine flame retardant, polyphosphate, and a combination or a single component formed by hydroxide and / or oxide.
3. The preparation method according to claim 2, characterized in that: The organic phosphorus system is selected from one or more mixtures of diethylaluminum phosphinate, diethylzinc phosphinate, and diethyl-monoethyl composite aluminum hypophosphite; the polyphosphate is selected from one or more mixtures of ammonium polyphosphate, piperazine pyrophosphate, and melamine polyphosphate; the hydroxide is selected from one or more mixtures of magnesium hydroxide and aluminum hydroxide; and the oxide is selected from one or more mixtures of zinc oxide and aluminum oxide.
4. The preparation method according to claim 3, characterized in that: The organic phosphorus flame retardant is aluminum diethylphosphinate, the polyphosphate is melamine polyphosphate, the combination or single component formed by the hydroxide and / or oxide is a 1:1 composition of magnesium hydroxide and zinc oxide, and the proportion of the three is 50-80:20-50:0.5-3.
5. The preparation method according to claim 1, characterized in that: The ester auxiliary agent is selected from tetraethyl orthosilicate and butyl titanate auxiliary agents; the alkaline coupling agent is selected from alkaline silane coupling agents; the lubricating dispersant is selected from zinc stearate, calcium stearate, glyceryl stearate, ethylene bisstearamide, silicone powder, oxidized polyethylene wax, montan wax and one or more mixtures thereof; the adhesive is selected from polyester modified silicone auxiliary agent, polyester modified siloxane, pentaerythritol stearate and oleamide.
6. The preparation method according to claim 1, characterized in that: The ester auxiliary agent is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, and the reaction is stirred at room temperature until the hydrolysis is completed.
7. The preparation method according to claim 1, characterized in that: The alkaline coupling agent is first dispersed in an alcohol solvent, and then pure water in a reaction molar equivalent is added, and the reaction is stirred at room temperature until the hydrolysis is completed.
8. A phosphorus-nitrogen composite carrier-free flame retardant masterbatch, which is prepared by the method according to any one of claims 1 to 7.
9. Application of the phosphorus-nitrogen composite carrier-free flame retardant masterbatch as claimed in any one of claims 1 to 7 in a glass fiber reinforced system for flame retardancy.
10. The use according to claim 9, characterized in that The ratio of the glass fiber reinforced system is: PA6 resin 50-55%, antioxidant 0.4-0.5%, glass fiber 30%, carrier-free flame retardant masterbatch 15%-20%.
Citation Information
Cited By
Flame-retardant BMC composite material and preparation process thereof
CN122502847A